Impact of process parameters on refused derived fuel pellets - Iqbal, MK; Nadeem, A; Butt, MT (Bangladesh Journal of Scientific and Industrial Research, 2020)
The objective of present study was to optimize the process conditions for the development of refused derived fuel (RDF) pellets from municipal solid waste (MSW) and biomass by using Response Surface Methodology (RSM). The three factors specifically moisture (20-45%), preheating temperature (50-120˚C) and pressure (500-1500 psi) were taken as center point. The experimental data of response variables were fitted into quadratic polynomial model using the multiple regression analysis and found it was statistically significant quadratic model and contour plot further revealed that moisture (20%), preheating temperature (120˚C) and hydraulic pressure (1000psi) were the best conditions. Moreover bulk density and durability of pellets increased due to temperature and pressure but decrease with moisture. The bulk density (BD) moisture durability (DU) size diameter carbon hydrogen sulpher chloride ash fixed carbon HHV (High heating value) LHV (Low heating value) and ash metal were also evaluated. Bangladesh J. Sci. Ind. Res.55(1), 73-82, 2020